Effectiveness and Immunogenicity of the MMR Vaccine Against SARS-CoV-2 Among Healthcare Workers - Seok, Hyeri; Bae, Joon-Yong; Kim, Jooyun; Choi, Won Suk; Park, Heedo; Lee, Jungmin; Lee, Sohyun; Kim, Chulwoo; Park, Man-Seong; Park, Dae Won (Viruses, 2025)
The purpose of this study was to evaluate the effectiveness and immunogenicity of the measles–mumps–rubella (MMR) vaccine against SARS-CoV-2 in healthcare workers at one medical institution. The effectiveness of the MMR vaccine against SARS-CoV-2 was evaluated in overall healthcare workers (HCWs). In addition, neutralizing antibodies to SARS-CoV-2 were measured according to the subjects’ measles immunity status with serum samples collected before the coronavirus disease 2019 pandemic period. The effectiveness of the MMR vaccine for SARS-CoV-2 in all HCWs and measles IgG-positive subjects was 34% (adjusted odds ratio [aOR] = 1.20, 95% confidence interval [CI] = 0.53–2.70) and 34% (aOR = 0.66, CI = 0.38–18.4), respectively. The neutralizing antibody levels for SARS-CoV-2 were low in all groups regardless of the measles immune status. The MMR vaccine alone may not provide sufficient protection against SARS-CoV-2.